2016
DOI: 10.5152/tud.2016.44442
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting liposomal bupivacaine decreases inpatient narcotic requirements in men undergoing penile prosthesis implantation

Abstract: Objective: A new extended-release bupivacaine suspension bupivacaine (ERSB) delivers 3 days of local anesthetic and has been shown to reduce pain and narcotic usage in some patient groups but this issue is largely unstudied in urologic surgery. Material and methods:We performed a single-surgeon retrospective chart review of the patients who underwent penile prosthesis implantation. Pain scores and standardized morphine equivalent (ME) dose data were collected during 23 hour-observation period. Subjects who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…BUP may be administered in 2 ways for implant surgery: by dorsal nerve block or by dipping the implant into BUP during surgery. Dorsal peripheral nerve block using BUP has shown promising results for postoperative pain reduction and control 17, 18. However, the effect of BUP dip on the antibiotic coating on penile implants has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…BUP may be administered in 2 ways for implant surgery: by dorsal nerve block or by dipping the implant into BUP during surgery. Dorsal peripheral nerve block using BUP has shown promising results for postoperative pain reduction and control 17, 18. However, the effect of BUP dip on the antibiotic coating on penile implants has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Cotta et al . found that men receiving an extended-release bupivacaine liposomal suspension had significantly decreased narcotic use after implantation relative to those who did not 25 . However, the authors reported significantly higher costs in the extended-release bupivacaine group, which may limit its routine use 25 .…”
Section: Peri-operative Pain Managementmentioning
confidence: 94%
“…found that men receiving an extended-release bupivacaine liposomal suspension had significantly decreased narcotic use after implantation relative to those who did not 25 . However, the authors reported significantly higher costs in the extended-release bupivacaine group, which may limit its routine use 25 . A variety of other local anesthetic approaches (dorsal penile nerve, pudendal nerve, crural, and intracorporal) and medications (lidocaine, bupivacaine, and ropivacaine) have been studied and employed with varying success 24, 26 .…”
Section: Peri-operative Pain Managementmentioning
confidence: 94%
“…The drain is not sewn in and the catheter is accessible through the dressing (a hole cut into the supportive undergarment) which facilitates removal of these items without disturbing the dressing as the patient removes 48 hours after surgery. Use of liposomal bupivacaine during the case aids in pain post procedure and minimizes narcotic use ( 6 ). We give 10 days of post-operative Bactrim although this practice admittedly has no evidence and probably treats the surgeon more than the patient.…”
Section: Post-operative Carementioning
confidence: 99%